Outdoor Behavioral Health Care: Client and Treatment Characteristics Effects on Young Adult Outcomes. (September 2016) - Roberts, Sean D.; Stroud, Daniel; Hoag, Matthew J.; Combs, Katie M.
A lack of clarity exists regarding how different clients respond to outdoor behavioral health care (OBH). In this study, specific client and treatment characteristics were assessed for 186 young adults completing an OBH therapeutic wilderness program. Clinical outcomes were measured with the Outcome Questionnaire–45.2. Hierarchical linear modeling results indicated no differences at intake, in change trajectories while in treatment, or at 6- and 18-months follow-up. Treatment gains and maintenance post-discharge were similar regardless of participant age, length of stay, gender, primary diagnosis, or therapist. Findings serve as additional support for the utility of OBH for a range of clients. Results are detailed and implications, limitations, and future research directions are discussed.